Hubungan Sikap Mengenai Pola Menyikat Gigi Terhadap Indeks DMF-T Pada Komunitas Pemberdayaan Perempuan Kepala Keluarga (Jurnal Terapi Gigi dan Mulut, 2023)
Dental and oral diseases that still occur in the community are dental caries. The method that is often used to measure dental caries status is the DMF-T index. One of the main factors that can affect the oral health of people in Indonesia is attitude. A person's attitude towards dental and oral health can determine the health status of his teeth and mouth. One of the actions that can be taken to prevent dental caries is through the attitude of a brushing pattern consisting of good and correct brushing time, technique, and frequency. This study aims to determine the relationship between attitudes regarding tooth brushing patterns on the DMF-T index in the Women Headed Family Empowerment Community (PEKKA) in Ciburial Village. This research method is non-experimental with quantitative analytic data collection and using a cross sectional hypothesis testing fisher exact. Samples were taken by total sampling with a total of 30 respondents. The results of this study obtained a significant relationship between attitudes regarding tooth brushing patterns on the DMF-T index in the Women Headed Family Empowerment Community (PEKKA) in Ciburial Village.